Soil diversity in terrestrial ecosystems of Antarctica (in the region of Russian Antarctic bases) - E. V. Abakumov; A. V. Lupachev (Ukrainian Antarctic Journal, 2012)
Data on soil formation in Antarctic discussed. Brief characteristics of soil diversity is given for landscapes in places of situation of Russian Antarctic stations. Main processes of soil formation described as well as conditions of this process realization.